2022
DOI: 10.3390/microorganisms10071375
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of PHMB and Other Guanidino Containing Compounds against Acanthamoeba and Other Ocular Pathogens

Abstract: In recent years, a rise in the number of contact lens users in the UK and worldwide coincided with an increased incidence of microbial keratitis. The aim of this study was to investigate the antimicrobial activities of polyhexamethylene guanidine (PHMG), polyaminopropyl biguanide (PAPB), and guazatine in comparison to the common contact lens disinfectant constituent, polyhexamethylene biguanide (PHMB). The study investigated these compounds against a broad range of organisms, including Acanthamoeba castellanii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other guanidino-containing compounds may exert similar anti-acanthamoebal effects to PHMB, such as polyhexamethylene guanidine (PHMG), polyaminopropyl biguanide (PAPB), and guazatine, though these have not been tested clinically [86]. Other antimicrobial agents including diamidines such as propamidine isethionate and hexamidine have also been used [87,88].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…Other guanidino-containing compounds may exert similar anti-acanthamoebal effects to PHMB, such as polyhexamethylene guanidine (PHMG), polyaminopropyl biguanide (PAPB), and guazatine, though these have not been tested clinically [86]. Other antimicrobial agents including diamidines such as propamidine isethionate and hexamidine have also been used [87,88].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…In 2022 the group of Heaselgrave et al published their research in to the use of PHMGH, polyaminopropylbiguanide (PAPB), and guazatine, in comparison to the contact lens disinfectant constituent polyhexamethylene biguanide (PHMB), for the treatment of ocular pathogens [ 38 ]. The researchers found that PHMGH was significantly more active (MIC: 0.5 μg/mL) than PHMB (MIC: 3.9 μg/mL) against a strain of Candida albicans .…”
Section: Introductionmentioning
confidence: 99%